2007
DOI: 10.1074/mcp.m700099-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

A High Content in Lipid-modified Peripheral Proteins and Integral Receptor Kinases Features in the Arabidopsis Plasma Membrane Proteome

Abstract: The proteomics of plasma membrane has brought to date only scarce and partial information on the actual protein repertoire. In this work, the plant plasma membrane proteome of Arabidopsis thaliana was investigated. A highly purified plasma membrane fraction was washed by NaCl and Na 2 CO 3 salts, and the insoluble fractions were further analyzed by nano-LC-MS/MS. With 446 proteins identified, we hereby describe the largest plasma membrane proteome diversity reported so far. Half of the proteins were predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
115
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 101 publications
(78 reference statements)
15
115
0
1
Order By: Relevance
“…2C). We conclude that wild-type HopAF1 and Arabidopsis MTNs interact specifically at the plasma membrane, as is consistent with the demonstrated localization of HopAF1 and with the observation that MTN1 and MTN2 may transiently localize to the plasma membrane via protein-protein interactions (60,62).…”
Section: Hr Triggered By Avrxv3 In Tomato Is Also Dependent On Its Pusupporting
confidence: 65%
“…2C). We conclude that wild-type HopAF1 and Arabidopsis MTNs interact specifically at the plasma membrane, as is consistent with the demonstrated localization of HopAF1 and with the observation that MTN1 and MTN2 may transiently localize to the plasma membrane via protein-protein interactions (60,62).…”
Section: Hr Triggered By Avrxv3 In Tomato Is Also Dependent On Its Pusupporting
confidence: 65%
“…Interestingly, both of the DHARs we found to be cytosolic were identified in a proteomics study of proteins associating with the plasma membrane, along with several other GSTs and peroxidases (Marmagne et al, 2007). Proteins other than the three DHARs, such as certain glutaredoxins or GSTs (Chew et al, 2003;Dixon et al, 2009), may be responsible for DHAR activities reported previously to be associated with the peroxisomes and mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cooperation between the DHARs, and particularly the cytosolic forms, is required to couple oxidative stress to the activation of downstream signaling. The importance of the cytosolic isoforms could be linked to their partial recruitment to the plasma membrane (Marmagne et al, 2007), possibly to set appropriate conditions for redox signaling at this location. However, the close correlation between glutathione and SA contents (Fig.…”
Section: Dhars Cooperate In Glutathione Oxidation Triggered By Oxidatmentioning
confidence: 99%
“…GPI-anchored proteins were annotated based on published literature and predictions (35)(36)(37). Graphs were created using SigmaPlot version 10 (Systat Software), and statistical tests were carried out using Excel Analyze-it package version 2.07.…”
Section: Fig 1 Work Flow Of the Reciprocal Labeling Experimentsmentioning
confidence: 99%